A simulation study for evaluating 'taxi' and 'bus' mode in same-day delivery. (19th April 2021) - Zhu, Yi; Zhao, Ning
Same-day delivery refers to the intra-city express of small goods, gifts and documents from sender to receivers. Same-day delivery currently adopts 'taxi' mode to complete the delivery as soon as possible with the sacrifice of lot scale economic benefits. Consequently, it is interesting that whether 'bus' mode featured with lot scale could dominate both in economic and delivery efficiency. To answer this question, simulation is employed to conduct a case study and compare the performance of 'taxi' mode and 'bus' mode. Further, two simulation scenario experiments are presented to find dominate conditions. Finally, we find that with limited distribution resources, 'taxi' mode can exploit advantages in the scenario of concentrated orders in space and low order volume, while 'bus' mode is more suitable for the scenario of wider delivery range and high order volume.